The Influence of Non-Financial Compensation and Competence on Employee Performance with Organizational Commitment as an Intervening Variable at PT Rangga Jaya Kontruksi - Millatul Islamiah Hs (Pustaka Digital Indonesia, 2025)
The growth of infrastructure in West Java has driven the expansion of the increasingly competitive construction sector. PT. Rangga Jaya Kontruksi Klapanunggal, as one of the construction companies in the region, faces challenges in maintaining employee performance, especially due to the decline in performance that occurred in 2023 compared to previous years. This decline can be seen in several key indicators, such as accuracy in completing tasks, teamwork, and compliance with occupational safety and health (K3) policies. This condition reflects the importance of a human resource management strategy that not only focuses on financial aspects, but also includes non-financial compensation, competency development, and strengthening organizational commitment. This study aims to analyze the effect of non-financial compensation and competency on employee performance, with organizational commitment as a mediating variable. The research method used is a quantitative approach by distributing questionnaires to 106 employees. The results of the study show that non-financial compensation and competency have a positive and significant effect on organizational commitment and employee performance. In addition, organizational commitment is proven to significantly mediate the relationship between the two independent variables and performance. These findings emphasize the importance of implementing a non-material reward system such as training, work flexibility, and achievement recognition, as well as project-based competency development. An organizational culture that encourages emotional attachment is also key to improving performance sustainably. Integration of these three aspects is necessary to strengthen the competitiveness of companies in the construction industry.